Ionization of the atomic gas in redshifted radio sources. Issue 1 (7th January 2019) - Curran, S J; Hunstead, R W; Johnston, H M; Whiting, M T; Sadler, E M; Allison, J R; Athreya, R
Abstract: We report the results of a survey for H i 21-cm absorption at $z$  ≲ 0.4 in a new sample of radio sources with the Giant Metrewave Radio Telescope. Of the 11 sources for which there are good data, we obtain zero detections, where four are expected upon accounting for the ionizing photon rates and sensitivity. Adding these to the previously published values, we confirm that the non-detection of 21-cm absorption in active sources at high redshift is due to photo-ionization of the gas rather than excitation by 21-cm photons (significant at 6.09σ and 2.90σ, respectively). We also confirm a strong correlation between the absorption strength and the reddening of the source, suggesting that dust plays a significant role in shielding the gas from the ambient ultraviolet field. An anticorrelation between the 21-cm detection rate and the radio turnover frequency is also found, which runs contrary to what is expected on the basis that the higher the turnover frequency, the more compact the source. It is, however, consistent with the hypothesis that the turnover frequency is related to the electron density, supported by a correlation between the turnover frequency and ionizing photon rate.